Thermal Regime of Rock and its Relation to Snow Cover in Steep Alpine Rock Walls: Gemsstock, Central Swiss Alps. Issue 3 (5th March 2015) - Haberkorn, Anna; Phillips, Marcia; Kenner, Robert; Rhyner, Hansueli; Bavay, Mathias; Galos, STEPHAN P.; Hoelzle, Martin
ABSTRACT Snow cover influences the thermal regime and stability of frozen rock walls. In this study, we investigate and model the impact of the spatially variable snow cover on the thermal regime of steep permafrost rock walls. This is necessary for a more detailed understanding of the thermal and mechanical processes causing changes in rock temperature and in the ice and water contents of frozen rock, which possibly lead to rock wall instability. To assess the temporal and spatial evolution and influence of the snow, detailed measurements have been carried out at two selected points in steep north‐ and south‐facing rock walls since 2012. In parallel, the one‐dimensional energy balance model SNOWPACK is used to simulate the effects of snow cover on the thermal regime of the rock walls. For this, a multi‐method approach with high temporal resolution is applied, combining meteorological, borehole rock temperature and terrain parameter measurements. To validate the results obtained for the ground thermal regime and the seasonally varying snowpack, the model output is compared with near‐surface rock temperature measurements and remote snow cover observations. No decrease of snow depth at slope angles up to 70° was observed in rough terrain due to micro‐topographic structures. Strong contrasts in rock temperatures between north‐ and south‐facing slopes are due to differences in solar radiation, slope angle and the timing and depth of the snow cover. SNOWPACK proved to be useful for modelling snow cover–rock interactions in smooth, homogenous rock slopes.